2022
DOI: 10.1126/science.abn0853
|View full text |Cite
|
Sign up to set email alerts
|

A specific circuit in the midbrain detects stress and induces restorative sleep

Abstract: In mice, social defeat stress (SDS), an ethological model for psychosocial stress, induces sleep. Such sleep could enable resilience, but how stress promotes sleep is unclear. Activity-dependent tagging revealed a subset of ventral tegmental area γ-aminobutyric acid (GABA)–somatostatin (VTA Vgat-Sst ) cells that sense stress and drive non–rapid eye movement (NREM) and REM sleep through the lateral hypothalamus and also inhibit corticotropin-releasing factor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 57 publications
5
52
0
1
Order By: Relevance
“…Gad1/Vgat, it is plausible that in the work of Yu et al a sizable population of the Sst neurons described here was responsible for the regulation. Interestingly, more recent work from the same laboratory identified, confirmed by our present findings, VTA Sst projections to the PVT and showed that this pathway regulates restorative sleep after stress (Yu et al, 2022). Here we, for the first time, to our knowledge, showed a direct connection between the VTA and alBNST through the Sst neurons.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Gad1/Vgat, it is plausible that in the work of Yu et al a sizable population of the Sst neurons described here was responsible for the regulation. Interestingly, more recent work from the same laboratory identified, confirmed by our present findings, VTA Sst projections to the PVT and showed that this pathway regulates restorative sleep after stress (Yu et al, 2022). Here we, for the first time, to our knowledge, showed a direct connection between the VTA and alBNST through the Sst neurons.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, similar increase in opioid sensitization resulting in higher morphine preference afterwards (Shaham et al, 1992) is often observed as a consequence of stressful events (Kalivas et al, 1986; Leyton and Stewart, 1990), also of emotional nature (Kuzmin et al, 1996). Since it also has been shown that deletion of the VTA Sst neurons disrupt normal restorative sleep after social defeat stress (Yu et al, 2022), it is possible to speculate that in both cases the VTA Sst neurons are involved in the adaptive changes of the VTA circuit which might occur only during sleep. The fact that morphine challenge in our experiments was done 7 days later also speaks in favour of this.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse models have greatly facilitated characterization of neural circuits controlling sleep-wake function that extend between neurons of prefrontal cortex and multiple ventral brain regions [13]. Particularly relevant to our current findings of increased sleep during the waking period after UCMS (Figures 5, 9) are elegant neural network studies that examined the response to stress and effects on sleep behavior [36]. These studies in male mice identified a midbrain circuit that responded to social defeat stress and induced sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Here we tested a stress induced by social defeat well known to modulate the amount of REM sleep. It is important to note that the effects of this type of stress on REM sleep vary according to the time of day it is initiated, the duration of the exposure to the aggressive mouse, and the chronicity or acuteness of the stress experience (Henderson et al, 2017; Wells et al, 2017; Yu et al, 2022). We confirmed the result of Henderson et al that REM sleep decreases after the stress protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Although the effects of stress on sleep can lead to serious health problems, we lack a clear picture of how stress impacts sleep. Indeed, depending on the type of stress, its duration of exposure, and the circadian period at which it occurs, the effects of stress on sleep can vary significantly, including fragmentation caused by multiple awakenings, a reduction or an increase of NREM or REM sleep (Pawlyk et al, 2008; Sanford et al, 2015; Antila et al, 2022; Yu et al, 2022). This complexity highlights the need to identify the different neural circuits that regulate the sleep response to stress in order to parse their contributions to specific aspects of sleep architecture.…”
Section: Introductionmentioning
confidence: 99%